„BARDZIEJ UBOGO, ALE PRZYZWOICIEJ” ODDZIAŁYWANIE RELIGIJNEGO KAPITAŁU SPOŁECZNEGO W POLSCE - Sadłoń, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The concept of social capital, which grew out of the economic context, is sometimes described in literature as a protection against economic inequality since it reduces deprivation and it is operationally associated and operatively associated with the process of sustainable development. Religion and religiousness are mentioned among the factors that generate social capital. On the other hand, a high level of religiosity, according to many international statistical analyses, is associated with low levels of macroeconomic indicators, including economic inequality. This article explores these relationships using a model of religious social capital. This model, used to describe the behavior of individuals and the characteristics of local communities in Poland, captures the relationship between religiosity, social capital and economic inequality. This relationship proves that on the one hand, religion is an important (principal) resource and a factor of social capital in Poland, on the other hand religious social capital coincides with economic inequality. In this respect the religious social capital differs from religion not based on social capital. However, religious social capital impacts on the moral sphere by reducing phenomena such as smoking, alcoholism, drug abuse and pill addiction.